Synthetic analogues of the montanine-type alkaloids with activity against apoptosis-resistant cancer cells. Issue 4 (15th February 2018) - Govindaraju, Karthik; Ingels, Aude; Hasan, Md Nabiul; Sun, Dandan; Mathieu, Veronique; Masi, Marco; Evidente, Antonio; Kornienko, Alexander
Graphical abstract: Abstract: In a search of small molecules active against apoptosis-resistant cancer cells, a skeletal rearrangement of alkaloid haemanthamine was utilized to generate a series of compounds possessing the alkaloid montanine ring system. The synthesized compounds were found to inhibit proliferation of cancer cells resistant to apoptosis at micromolar concentrations. Selected compounds were also active against patient-derived glioblastoma cells expressing stem-cell markers. This is the first report describing the preparation of synthetic analogues of the montanine-type alkaloids with antiproliferative activity. The compounds prepared in the current investigation appear to be a useful starting point for the development of agents to fight cancers with apoptosis resistance, and thus, associated with poor prognoses.